2008
DOI: 10.1007/s12548-008-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Inclination of mandibular canine in relation to the condylo-occlusal line

Abstract: Statement of problem: Geometrically, to best resist occlusal forces, the mandibular incisor presents generally an orthogonal inclination (approximately 90 ) to the radius of rotation during the closing movement of the mandible, the centre of rotation being the condyles.Purpose: The objective of this study was to confirm the application of this geometrical principle, named "tangent law", to the inclination of the mandibular canine. If the tangent law is applicable to the mandibular canine, the mean angle betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…These values are 15 for a third molar, 20 for a second molar, 25 for a first molar, 28 for a second premolar and the mean differential angle was close to 0 for incisors, and a recent paper showed that the mandibular canine inclination follow the same rule [7]. On the posterior teeth, the differential angle leads to horizontal components of force tending to tilt the posterior teeth forward.…”
Section: Introductionmentioning
confidence: 83%
“…These values are 15 for a third molar, 20 for a second molar, 25 for a first molar, 28 for a second premolar and the mean differential angle was close to 0 for incisors, and a recent paper showed that the mandibular canine inclination follow the same rule [7]. On the posterior teeth, the differential angle leads to horizontal components of force tending to tilt the posterior teeth forward.…”
Section: Introductionmentioning
confidence: 83%